2021
DOI: 10.1021/acsptsci.1c00016
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Proteomics Analysis of Anti-COVID-19 Nucleoside and Nucleotide Prodrug-Activating Enzymes Provides Insights into the Optimization of Prodrug Design and Pharmacotherapy Strategy

Abstract: Nucleoside and nucleotide analogs are an essential class of antivirals for COVID-19 treatment. Several nucleoside/nucleotide analogs have shown promising effects against SARS-CoV-2 in vitro ; however, their in vivo efficacy is limited. Nucleoside/nucleotide analogs are often formed as ester prodrugs to improve pharmacokinetics (PK) performance. After entering cells, the prodrugs undergo several enzymatic metabolism steps to form the active metabolite triphosphate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…A more recent study, however, demonstrated that human lung tissues also have sufficient CatA and CES1 to activate RDV [13]. Our recent study found that CES1 protein abundance was over 200-fold higher in the liver than in the lung, while CatA protein expression was comparable between the lung and the liver [16]. As such, we hypothesized that a greater susceptivity to CatA and lower susceptivity to CES1 might facilitate the pulmonary activation of a ProTide.…”
Section: Methodsmentioning
confidence: 89%
See 4 more Smart Citations
“…A more recent study, however, demonstrated that human lung tissues also have sufficient CatA and CES1 to activate RDV [13]. Our recent study found that CES1 protein abundance was over 200-fold higher in the liver than in the lung, while CatA protein expression was comparable between the lung and the liver [16]. As such, we hypothesized that a greater susceptivity to CatA and lower susceptivity to CES1 might facilitate the pulmonary activation of a ProTide.…”
Section: Methodsmentioning
confidence: 89%
“…Proteomics data were analyzed using the Spectronaut Pulsar software (version 11.0; Biognosys AG, Schlieren, Switzerland) with a spectral library generated from pooled HLS9 and HlungS9 in a previous study [16] and the human proteome FASTA file downloaded from UniProtKB. The human serine hydrolases proteomics data were extracted using a FASTA file containing 238 human serine hydrolases [16]. The normalized abundance of a specific serine hydrolase was the ratio of its intensity to the intensity of biotinylated BSA (internal standard) in each sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations